Oxygen uptake in the vitamin B2-sensitized photo-oxidation of tyrosine and tryptophan in the presence of uracil: Kinetics and mechanism - Montaña, Maria Paulina (2009)
Considering the significance of visible light-promoted reactions in complex biological media, the photo-oxidation of the amino acids (AAs) tyrosine (tyr) and tryptophan (trp) was studied in the presence of the naturally occurring oxidative scavenger uracil (ur). The involved photoprocesses, studied at pH 7 and 9, are driven through the reactive oxygen species (ROS) singlet molecular oxygen (O2(1Äg)), superoxide radical anion (O2•−) and hydrogen peroxide (H2O2). The effect on the effectiveness of the overall photo-oxidation process due to the presence of an added electron-donating substrate such as ur is not straightforwardly predictable. The addition of the pyrimidine compound, a much lesser photo-oxidizable substrate than the AAs themselves, produced different results: (1) antioxidative for tyr at pH 9, decreasing the overall rate of oxygen uptake; (2) synergistic for tyr at pH 7, increasing the oxidation rate more than the corresponding addition value of the respective individual rates and (3) no effect for trp at both pH values. The final result depends on the respective abilities of the substrates as quenchers of both the long-lived riboflavin triplet excited state and the generated ROS and the pH of the medium. An interpretation for the different cases is attempted through a kinetic and mechanistic analysis.